Risk Management of Accounting Firms in the Digital Era - Kittiwisedkul, Phatcharaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
Currently, our world is changing rapidly. Especially the technology has transformed into the digital era. All organizations, including accounting firms, face an increased organizations strategic risk and new risk in the digital era. This article has the objective to study the approaches for risk management of technological changes in accounting firms, so that these firms can prepare with the changes that are occurring. Many organizations have adapted by applying technology to improve their work operations. For example, the organizations use cloud technology, host via the internet for data storage, processing, and more; robotic process automation, robot that work automatically on a computer system; blockchain technology, account storage technology; data analytics technology; application programing interface, data transmission technology; and cybersecurity technology. The accounting firms can apply risk management framework of the COSO ERM 2017 in the organization’s operations to suit each organization. Firstly, leaders set the direction for operations, goals, strategies, and risk management policies, particularly technology risks. They should also select a risk management approach that responds to risks at an acceptable level. Additionally, they should communicate with everyone in the organization about the organization’s strategies and policies, as everyone is involved in defining and responsibility for the risk management process. After that, they must continuously review, assess, improve, and monitor risk management process. Therefore, the fundamental principle of COSO ERM 2017 that should be emphasized is the governance of operations to achieve objectives and the creation of an organizational culture that focuses on developing personnel skills, promoting the learning of new technologies, and raising awareness of cybersecurity. In addition, the accounting firms should study investment information and the returns from the implementation of technology, ensuring that it is a worthwhile investment. This will lead to more efficient work processes and drive the organization to achieve its goals in the digital era. Article history: Received 16 May 2025 Revised 5 November 2025 Accepted 7 November 2025 SIMILARITY INDEX = 6.41 %